2011
DOI: 10.4161/psb.6.3.13881
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance transport of signals during symbiosis

Abstract: Legumes enter nodule symbioses with nitrogen-fixing bacteria (rhizobia), whereas most flowering plants establish symbiotic associations with arbuscular mycorrhizal (AM) fungi. Once first steps of symbiosis are initiated, nodule formation and mycorrhization in legumes is negatively controlled by a shoot-derived inhibitor (SDI), a phenomenon termed autoregulation. According to current views, autoregulation of nodulation and mycorrhization in legumes is regulated in a similar way. CLE peptides induced in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 70 publications
(112 reference statements)
1
10
0
Order By: Relevance
“…We observed that differing levels of AMF inoculum availability resulted in differences in the magnitude and direction of herbivore-induced defenses, despite resulting in similar levels of root colonization. Plants maintain a maximum level of AMF colonization and suppress further colonization (Vierheilig et al 2000a, b, Vierheilig 2004, Meixner et al 2005) by regulating phytohormones, including JA and SA (Staehelin et al 2011, Gutjahr 2014, Bucher et al 2014). These hormones play key roles in the regulation of resistance responses of plants to insect herbivores (Pieterse et al 2012(Pieterse et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that differing levels of AMF inoculum availability resulted in differences in the magnitude and direction of herbivore-induced defenses, despite resulting in similar levels of root colonization. Plants maintain a maximum level of AMF colonization and suppress further colonization (Vierheilig et al 2000a, b, Vierheilig 2004, Meixner et al 2005) by regulating phytohormones, including JA and SA (Staehelin et al 2011, Gutjahr 2014, Bucher et al 2014). These hormones play key roles in the regulation of resistance responses of plants to insect herbivores (Pieterse et al 2012(Pieterse et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the host Autoregulation of Nodulation (AON) and Autoregulation of Mycorrhization (AOM) pathways that control the extent of nodulation and mycorrhization, respectively. 3,4 Classical plant hormones play crucial roles in the nodulation and mycorrhization processes. [5][6][7] Some fundamental effects of these hormones on the gross level of colonisation are compared for the 2 symbioses in Table 1.…”
mentioning
confidence: 99%
“…Although AMF colonization levels increase with increasing inoculum availability (Garrido et al, 2010;Vannette and Hunter, 2011), plants maintain a maximum level of AMF colonization of roots (Vierheilig et al, 2000a,b;Meixner et al, 2005) and suppress further colonization after reaching a critical level (Vierheilig, 2004). Plant regulation of AMF development in roots is controlled by the same plant hormones (Staehelin et al, 2011;Bucher et al, 2014;Gutjahr, 2014;and references therein) that are integral to the development of plant vascular tissues (Lucas et al, 2013) and the resistance responses of plants to insect herbivores (Pieterse et al, 2012(Pieterse et al, , 2014. In our medium AMF treatment, there may have been sufficient inoculum to attain maximum levels of AMF colonization of plant roots.…”
Section: Discussionmentioning
confidence: 99%